Alerta Cannabis: A Tailored-Computer Web-Based Program for the Prevention of Cannabis Use in Adolescents: A Cluster-Randomized Controlled Trial Protocol - Marta Lima-Serrano; Carmen Barrera-Villalba; Isotta Mac-Fadden; Ilse Mesters; Hein de Vries (BMC, 2024)
Abstract Background The growing use of cannabis in adolescence is a public health problem that must be addressed through prevention. In Spain, the average age of initiation of cannabis use in the adolescent population is 14.8 years. At 14 years, the lifetime prevalence of cannabis use is 11.7%, which increases to 51.,5% at the age of 18; the prevalence of cannabis use in the population aged 14 to 18 years is 28.6%, a figure that must be tried to reduce, that is why this school prevention program is proposed: Alerta Cannabis. Methods The Alerta Cannabis research project consists of design, implementation, and evaluation. In the first phase, a computer-tailored eHealth program (Alerta Cannabis) is developed based on the I-Change Model, an integrated model based on three main behavioral change processes: awareness, motivation, and action. This program consists of four 30-minute sessions that will provide culturally adapted and personalized advice to motivate students not to use cannabis through text feedback, animations, and gamification techniques. This phase will also include usability testing. In the implementation phase, secondary school students from Western Andalusia, Spain (Seville, Cádiz, Huelva, and Córdoba) and Eastern Andalusia (Jaén, Málaga, and Granada) will be randomized to an experimental condition (EC) or a control condition (CC) for a cluster randomized clinical trial (CRCT). Each condition will have 35 classes within 8 schools. GI will receive the online intervention Alerta Cannabis. EC and CC will have to fill out a questionnaire at baseline, six months, and twelve months of follow-up. In the last phase, the effect of Alerta Cannabis is evaluated. The primary outcomes are the lifetime prevalence of cannabis use and its use in the last 30 days and at 6 months. At 12 months of follow-up, the prevalence in the last 12 months will also be assessed. The secondary outcome is the intention to use cannabis. Discussion The study tests the effect of the innovative program specifically aimed to reduce the use of cannabis in the adolescent population through eHealth in Spain. The findings aim to develop and implement evidence-based cannabis prevention interventions, which could support school prevention, for instance, the assistance of school nurses. If the program proves to be effective, it could be useful to prevent cannabis use on a national and international scale. Trial registration NCT05849636. Date of registration: March 16, 2023.